IMPLEMENTATION OF MIND MAPPING LEARNING ON STUDENTS' CREATIVE THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Laelatul Chodriyah; Murtono Murtono; Santoso Santoso; Erik Aditia Ismaya (Universitas Muria Kudus, 2021)
The purpose of this study was to analyze the effect of the mind mapping learning model on the ability to think creatively in material styles in elementary schools.This type of research is quantitative with a quasi experimental approach with the form of non equivalent control group design. The research population was the fourth grade students of SD in Dempet District. The research sample for grade IV SD N Kedongori, grade IV SD N Kebonsari 2 and grade IV SD N Balerejo 1. The sampling choice in this study was the purposive sampling technique. The data collection techniques used were observation, questionnaires and written tests. Data analysis includes data descriptions, analysis prerequisite tests, and hypothesis testing using the t test.The results of the study with the t test for the test instrument t count bigger than t table (15,956 bigger than 2,086). The results of the t test on the questionnaire instrument t value bigger than t table (9,201 bigger than 0.05). The conclusion is that there is an effect of mind mapping learning on the ability to think creatively in elementary school students